IMPACT OF MONETARY REFORM OF THE 1920S ON BUDGETARY RELATIONS IN UKRAINIAN SSR - Чеберяко, О. В. (Scientific Progress & Innovations, 2014)
Formation and functioning of the soviet budgetary system in Ukrainian SSR in the 1920th was impossible without monetary reform, and the realization of this reform in 1922-1924 promoted to organizationally - functional arrangement of the budgetary system, forming of permanent indexes of profitable and expendable parts, state and local budgets, that the so-called fixed budget. It is shown that from the point of view of the budgetary financing, a soviet banknote («sovznak»), that is money of treasury, undertook the basic load during 1921–1924. A soviet banknote even guarded tchervonets from depreciation in the period of introduction as new monetary unit. Therefore, determining influence of monetary reform on a budgetary process, it should to take into account all stages of monetary reform and correlation of pre-war rouble of and so called trade, conditional gold rouble. In the conditions of statement of fixed currency – tchervonets – for stabilizing the budgetary system and budgetary relations it was important to protect tchervonets from depreciation, to prevent the role of emission mean. It was necessary to avoid emission in budgetary profits, to use budgetary expenditures economically, to plan the budget responsibly, to consider financial sources carefully.